The Influence of Organizational Factors and Customer Orientation on Hotel Performance through Hotel Customer Orientation Agility in Star-Rated Hotels in Central Java - Erny Kusmastuti; Denny Bernadus; Timotius Febry (CV. Creative Tugu Pena, 2026)
The rapid growth of the tourism industry has intensified competition within the hotel sector, compelling hotel management to enhance performance to maintain customer appeal. This study aims to analyze the influence of Organizational Factor, Customer Orientation, and Competitive Environment on Hotel Performance in five-star hotels in Central Java, employing a quantitative explanatory design with data collected through questionnaires distributed to 134 respondents selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and fuzzy-set Qualitative Comparative Analysis (fsQCA). The PLS-SEM results indicate that Customer Orientation and Competitive Environment have significant positive effects on Hotel Performance, whereas Organizational Factor shows no substantial direct effect; however, all three variables collectively strengthen hotels' organizational capability. The fsQCA results complement these findings by demonstrating that no single condition independently determines Hotel Performance; instead, high performance is achieved through three alternative causal configurations: Competitive Environment and Customer Orientation, Competitive Environment and Organizational Factor, and Customer Orientation and Organizational Factor. Taken together, the integrated findings reveal that hotel performance is predominantly driven by the ability to understand customer needs and respond to competitive pressures. At the same time, organizational factors become influential when they operate in combination with other conditions within specific configurational patterns. Hotel management can utilize customer relationship management (CRM) systems integrated with market analytics platforms to capture customer behavior and monitor competitor strategies. In addition, regular workshops can be conducted to equip employees with the skills required to respond effectively to competitive pressures. Furthermore, hotels should implement standard operating procedures (SOPs) that prioritize service personalization based on customer profiles